2008
DOI: 10.2214/ajr.08.1218
|View full text |Cite
|
Sign up to set email alerts
|

Incremental Value of Diagnostic 131I SPECT/CT Fusion Imaging in the Evaluation of Differentiated Thyroid Carcinoma

Abstract: Iodine-131 SPECT/CT is useful for accurate evaluation of regional and distant activity in characterization of foci as residual thyroid tissue or nodal, pulmonary, or osseous metastasis. Suspected physiologic mimics of disease can be confirmed with increased reader confidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
6

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(59 citation statements)
references
References 10 publications
3
50
0
6
Order By: Relevance
“…Rapid exclusion of physiologic activity or contamination resulted in elimination of equivocal interpretations on planar scans. Reader confidence increased for interpretation of 104 of 147 foci (71%) seen on planar images after the review of SPECT/CT (67).…”
Section: Utility Of Diagnostic Preablation Radioiodine Spect/ctmentioning
confidence: 99%
“…Rapid exclusion of physiologic activity or contamination resulted in elimination of equivocal interpretations on planar scans. Reader confidence increased for interpretation of 104 of 147 foci (71%) seen on planar images after the review of SPECT/CT (67).…”
Section: Utility Of Diagnostic Preablation Radioiodine Spect/ctmentioning
confidence: 99%
“…In addition, physiological I-131 uptake in the salivary glands, nose, mouth and residual thyroid tissue is also an important problem because some abnormal foci of activities can be hidden by these overlapping structures [8][9][10][11]. In some studies, SPECT/CT was performed on only selected patients whose planar images showed inconclusive findings [11,12]. Chen et al [11] reported that SPECT/CT was of incremental value over planar I-131 WBS in increasing accuracy, reducing pitfalls and modifying therapy in 73.9% of patients with DTC.…”
Section: Discussionmentioning
confidence: 99%
“…The identified I-131 and I-123 SPET-CT studies concerned patients prepared with either endogenous hypothyroidism or exogenous recombinant human TSH stimulation, and they used diagnostic imaging doses ranging from 37 to 430 MBq (1-11 mCi) [19][20][21][22][23][24] and post-therapy imaging doses ranging from 1.1 to 9.7? GBq (30-260?…”
Section: Study Characteristics and Protocols For Spet-ctmentioning
confidence: 99%
“…mCi) [20,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. Radioiodine SPET-CT was used for surveillance for thyroid cancer recurrence, before I-131 therapy [19,20,27,41,42], in the post-surgical setting for radioiodine ablation of normal thyroid remnants, [21,22,24], or in post-therapy imaging [25-30, 32, 33, 36, 37, 39, 40, 43-45].…”
Section: Study Characteristics and Protocols For Spet-ctmentioning
confidence: 99%